PSYCHOMETRIC PROPERTIES OF THE NATURE RELATEDNESS SCALE (NRS) IN THE ITALIAN CONTEXT - Daniela PAOLETTI; Simona DE STASIO; Benedetta RAGNI; Antonino CALLEA; Nicoletta ROSATI; Carmen BERENGUER; Maria CINQUE; Elizabeth NISBET (Anthropological Researches and Studies)
Objectives. Nature Relatedness encompasses affective, cognitive, and experiential aspects of individuals’ connection with nature and refers to the appreciation and understanding of our interconnectedness with all other living things on Earth. This study aims to validate the Nature Relatedness Scale (NRS) in its Italian version, adapting and testing its reliability and validity in the Italian cultural context. A secondary objective is to analyze associations between NRS, pro-environmental orientation, and mindfulness. Material and methods. The study sample consisted of 388 Italian adults aged between 18 and 84 years (72.7% women; M age 32.7 years). Participants completed the following questionnaires: Nature Relatedness Scale (NRS); New Ecological Paradigm Scale (NEP); Mindfulness Awareness Attention Scale (MAAS). To test the scale’s adherence to the Italian context a confirmatory factor of analysis (CFA) was performed, and the correlation analysis were conducted to test the association between variables. Results. Italian NRS has shown good internal consistency (α = 0.85; ω = 0.86). The CFA highlighted acceptable of fit to our data supporting the use of NRS to measure Nature Relatedness in Italian adults. Moreover, the correlation between the NRS and NEP was significantly positive (r = 0.459 p = < .001), also the associations between NRS and MAAS showed similar results (r = 0.180 p = < .001). Conclusions. Taking into account the good psychometric properties of the NRS Italian version it could be useful in psychological research to explore all the factors that might play key roles in the human-nature link. These results could also be helpful in promoting programs and interventions to increase people’s well-being and environmental protection.